2018
DOI: 10.1038/s41418-018-0088-5
|View full text |Cite
|
Sign up to set email alerts
|

Cell-autonomous and cell non-autonomous downregulation of tumor suppressor DAB2IP by microRNA-149-3p promotes aggressiveness of cancer cells

Abstract: The tumor suppressor DAB2IP contributes to modulate the network of information established between cancer cells and tumor microenvironment. Epigenetic and post-transcriptional inactivation of this protein is commonly observed in multiple human malignancies, and can potentially favor progression of tumors driven by a variety of genetic mutations. Performing a high-throughput screening of a large collection of human microRNA mimics, we identified miR-149-3p as a negative post-transcriptional modulator of DAB2IP.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 47 publications
1
40
0
Order By: Relevance
“…It has been reported that miR-149-3p plays a vital role in various cancers and is induced by some antitumor drugs [36,37,53]. Notably, we found that DCA treatment could induce the binding of p53 to the upstream region (−677 to −477) of miR-149 and that miR-149-3p was upregulated by DCA treatment in a p53-dependent manner.…”
Section: Discussionmentioning
confidence: 48%
“…It has been reported that miR-149-3p plays a vital role in various cancers and is induced by some antitumor drugs [36,37,53]. Notably, we found that DCA treatment could induce the binding of p53 to the upstream region (−677 to −477) of miR-149 and that miR-149-3p was upregulated by DCA treatment in a p53-dependent manner.…”
Section: Discussionmentioning
confidence: 48%
“…For examples, Ru et al demonstrated that miR‐149‐3p was involved in the mechanisms of voltage‐gated K + channels in mediating cell proliferation and apoptosis in human glioma U87‐MG cells , but the specific regulatory molecule mechanism was not clear. In tumor endothelial cells, miR‐149‐3p facilitated the activation of nuclear factor kappa B (NF‐κB) signaling and promoted expression of pro‐inflammatory and pro‐angiogenic factors . Chamorro‐Jorganes et al reported that both miR‐149 and miR‐149* up‐regulated angiogenic responses by regulating fibroblast growth factor 2 but lowered the number of HUVECs .…”
Section: Discussionmentioning
confidence: 99%
“…miR-214 overexpression in synovial sarcoma cells did not promote cell growth, migration, nor invasion abilities in vitro, suggesting that it might promote tumor development in a cell non-autonomous manner [34,35]. Gene expression profiling revealed upregulation of inflammatory cytokine genes in synovial sarcoma with miR-214 overexpression.…”
Section: Discussionmentioning
confidence: 93%